The Relationship between Organizational Spirituality, Organizational Commitment, and Organizational Ethics among Elementary School Managers - Fatemeh Alipour; Zahra Aghaali (Iranian Evolutionary Educational Psychology Journal, 2023)
Objective: The purpose of this research is to investigate the relationship between organizational spirituality, organizational commitment, and organizational ethics among male elementary school managers in Qom city in 2022. Methods: This study is applied in terms of its objective and correlational in terms of the method used. The statistical population of the research includes all male managers at the elementary level in Qom city, totaling 360 individuals. Using multi-stage sampling, a sample of 81 individuals was selected. They were evaluated using Milliman et al.'s (2003) Organizational Spirituality Questionnaire, Allen and Meyer's Organizational Commitment Questionnaire, and Hunt et al.'s Organizational Ethics Questionnaire. Descriptive and inferential statistical methods (multiple regression) were employed for data analysis. Results: The results indicate a significant positive relationship between organizational spirituality, organizational commitment, and organizational ethics among the managers. Moreover, each dimension of organizational spirituality has a positive and significant relationship with organizational commitment and organizational ethics. Conclusions: Confirming the relationship between organizational spirituality, organizational commitment, and organizational ethics suggests that managers' attitudes towards spirituality can help improve employees' commitment and ethical conduct, consequently leading to overall organizational performance enhancement. Therefore, serious attention should be paid to the concept of organizational spirituality, and efforts should be made to enhance it.